In vitro organogenesis in Albizia guachapele, Cedrella odorata and Swietenia macrophylla (Fabaceae, Meliaceae) - Valverde Cerdas, Lisette (Universidad de Costa Rica, 1998)
Regeneration of adventitious buds was achieved from hypocotyl explanls of Albizia guachapele (Guayaquil) and Cedrella odorata (Spanish cedar), and from epicotyl explants from Swietenia macrophylla (Honduran Mahogany). Seeds were obtained from CATIE's Latin American Fores! Seed Bank and genninated under aseptic conditions .. Four explants were cultured in each Petri dish on half strength modified Murashige and Skoog basal medium, and five concentrations of BA (benzyladenine) were studied; A. guachapele and S. macrophylla responded positively lo the presence of BA in the culture medium. Otherwise, Cedrella odorata requíred media supplemented with citokinin and auxin combinations lo induce adventitious buds.